Virtual Energy Management for Physical Energy Savings in a Legged Robot Hopping on Granular Media - Roberts , Sonia F.; Koditschek, Daniel E. (Frontiers in Robotics and AI, 2021)
We discuss an active damping controller to reduce the energetic cost of a single step or jump of dynamic locomotion without changing the morphology of the robot. The active damping controller adds virtual damping to a virtual leg spring created by direct-drive motors through the robot's leg linkage. The virtual damping added is proportional to the intrusion velocity of the robot's foot, slowing the foot's intrusion and thus the rate at which energy is transferred to and dissipated by the ground. In this work, we use a combination of simulations and physical experiments in a controlled granular media bed with a single-leg robot to show that the active damping controller reduces the cost of transport compared with a naive compression-extension controller under various conditions.